Chorda tympani nerve dysfunction associated with congenital microtia. (3rd July 2017) - Takano, Kenichi; Takahashi, Nozomi; Ogasawara, Noriko; Yotsuyanagi, Takatoshi; Himi, Tetsuo
Abstract: Conclusion: This is the first report to investigate the correlation between ear anomalies related to the development of specific ear structures and chorda tympani dysfunction (CTD) in congenital microtia. CTD is not always consistent with the severity of the ear anomaly or the presence of facial nerve paralysis (FNP). Objectives: To investigate the relationship between the severity of ear anomalies and CTD as well as FNP in congenital microtia. Methods: A retrospective assessment was performed for all patients with microtia over the period 2010–2016. All ears were graded based on the severity of ear deformity using the Jahrsdoerfer system, based on findings on computed tomography of the temporal bone. Electrogustometry (EGM) was performed to evaluate CTD. Results: The group included 110 male and 62 female patients. The right ear was the most commonly affected (right 106, left 47). Eighteen patients (10.5%) had abnormal EGM thresholds. The mean (± SD) Jahrsdoerfer scores in the without CTD and positive for CTD groups were 6.53 ± 0.32 and 7.06 ± 0.37, respectively. In terms of sub-total points, there was no significant correlation between anatomic structure and CTD. There was no significant correlation between CTD and the presence of FNP.